Intake, sources, and determinants of free sugars intake in Australian children aged 12–14 months - Devenish, Gemma; Ytterstad, E.; Begley, Andrea; Do, L.; Scott, Jane (Wiley-Blackwell Publishing, 2018)
© 2018 John Wiley & Sons Ltd The consumption of free sugars is directly associated with adiposity and dental caries in early childhood; however, intake data in the first 2 years of life are limited. This cross-sectional analysis aims to identify major food sources of free sugars for Australian children aged 12–14 months and investigate factors associated with meeting the World Health Organisation (WHO) Guideline for sugars intake. Three days of nonconsecutive dietary data were collected via a 24-hr recall and 2-day food record for 828 participants. Usual intake of energy, total sugars, and free sugars were estimated, along with food group contributions to free sugars. Multiple logistic regression analysis was used to investigate factors associated with exceeding the WHO conservative recommendation that <5% of energy should come from free sugars. Mean free sugars intake was 8.8 (SD 7.7, IQR 3.7–11.6) g/day, contributing 3.6% (SD 2.8, IQR 1.6–4.8) of energy. Only 2.4% of participants exceeded the WHO recommendation that <10% of energy should come from free sugars, with 22.8% of participants exceeding the <5% recommendation. Children from households with greater socio-economic disadvantage (IRSAD <5, OR = 1.94) and in the lowest income bracket (OR = 2.10) were more likely to have intakes =5% of energy. Major food sources of free sugars were commercial infant foods (26.6%), cereal-based products (19.7%), namely, sweet biscuits (8.3%) and cakes (7.6%), followed by yoghurt (9.6%), and fruit and vegetable beverages (7.4%). These findings highlight the substantial contribution of infant foods to free sugars intakes and provide further evidence that dietary intakes are influenced by social determinants.